Multidisciplinary coordinated caregiving : research • practice • policy - Travis, Shirley S.; Talley, Ronda C. (Caregiving: Research • Practice • Policy, 2014)
Effective, meaningful caregiving requires a well-coordinated and informed effort guided by various highly skilled specialists across several interrelated professions, including psychologists, social workers, and occupational therapists. Multidisciplinary Coordinated Caregiving addresses the information needs of these interrelated professionals, contributing to the direct care of individuals and serving as an essential resource for those who ultimately create collaborative approaches to contemporary caregiving plans. In addition, the volume provides a wealth of evidence-based research findings to facilitate ongoing dialogue about multidisciplinary and interdisciplinary perspectives on and interventions for the complex challenge of caregiving in America. Key areas of coverage include: The status of professional caregiving in the United States. Nursing perspectives on the state of family caregiving. Psychological aspects of caregiving. A human development, lifespan perspective on caregiving during late life. Public health contributions to caregiving. Multidisciplinary Coordinated Caregiving offers a wealth of insights for those researchers, practitioners, and graduate students who seek to optimize the care of individuals across such fields as psychology, social work, public health, geriatrics and gerontology, and medicine as well as public and educational policy making.